ORGANISING THE TEACHING OF FINANCIAL ELEMENTS IN UPPER-SECONDARY MATHEMATICS THROUGH MATHEMATICAL MODELLING ACTIVITIES - Tien Dat, Nguyen (HNUE Journal of Science: Journal of Educational Science, 2025)
In many countries, finance is regarded as a key content area to be integrated into the general education curriculum, particularly in mathematics. Drawing on both international and domestic studies, this paper proposes a pedagogical procedure for teaching financial elements in upper-secondary mathematics through mathematical modelling activities and illustrates its appropriateness with concrete examples.